Utility of the prostest to predict and monitor response to chemotherapy in metastatic Castration-Resistant prostate cancer: A prospective pilot study - Kambiz Rahbar; Katrin Schlack; Martin Bögemann (BMC Cancer)
Abstract Background Metastatic castration-resistant prostate cancer (mCRPC) treatment has advanced with therapies such as androgen receptor pathway inhibitors (ARPIs), taxane chemotherapies like docetaxel, and novel agents like 177Lu-PSMA. However, predicting patient responses and sequencing therapies remain critical unmet needs. This study investigated whether the PROSTest, a molecular assay analyzing prostate cancer-specific transcripts, could predict treatment response or prognosis in mCRPC patients receiving docetaxel, compared to changes in prostate-specific antigen (PSA) levels. Methods Nineteen patients with mCRPC were treated with a median of 10 docetaxel cycles. PROSTest, which measures tumor-related signaling pathways, was analyzed via qPCR, while PSA levels were determined using standard clinical assays. PSA and PROSTest scores were measured at baseline and after one treatment cycle. PROSTest, which evaluates tumor-related signaling pathways, was analyzed via qPCR, and prostate-specific antigen (PSA) levels were measured using standard clinical assays. Responses were categorized per Prostate Cancer Working Group 3-criteria. Associations between biomarker changes, progression-free survival (PFS), and overall survival (OS) were evaluated using Kaplan-Meier survival analysis and hazard ratios (HRs). Results Baseline PSA and PROSTest scores did not predict response or survival. However, early changes in both biomarkers after one treatment cycle significantly correlated with PSA-PFS. PROSTest changes demonstrated a stronger association with PFS (HR: 0.04) compared to PSA (HR: 0.2). Early changes in PROSTest were also significantly (p = 0.03, AUC = 0.81 ± 0.14) associated with OS in contrast to PSA changes. Conclusions This pilot study suggests that PROSTest may offer superior predictive and prognostic value compared to PSA in mCRPC patients undergoing docetaxel therapy. Larger, multicenter studies are needed to confirm these findings and validate the assay’s clinical integration. Trial registration NCT06872619.